The Impact of Bamboo Cavities on Thermal Comfort in Building Construction - Modiano, Jovanny Yves; Wijaya, Phoebe Anthonieta Danny; Putra, Heristama Anugerah (CV. Gio Architect, 2024)
In tropical countries like Indonesia, bamboo stands out as a sturdy and readily available building material due to its rapid growth. It's widely utilized in forming structural and architectural elements of buildings. However, due to the complexity of connections, bamboo has seen some replacement by newer materials like brick, steel, and concrete. Yet, the resurgence of bamboo usage aligns with the emergence of the green building concept, prioritizing environmentally friendly materials sourced from the local environment. Bamboo finds extensive application in tropical housing, serving as columns, roofs, and walls, often woven. This material effectively reduces indoor temperatures, providing occupants with thermal comfort. However, there's a gap in understanding regarding the use of bamboo as log-shaped walls or the role of cavities in bamboo stems in enhancing thermal comfort. This study adopts a quantitative approach, primarily through literature review, employing a descriptive presentation method. Bamboo plays a significant role in lowering room temperatures, particularly due to its cavity structure, which facilitates heat dissipation. This makes it suitable for use in tropical areas as a material for residential houses and other buildings.